Study of resonance conditions on higher harmonics in an electrical network supplying a nonlinear load - E. V. Zubova; D. S. Fedosov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. The increase in the share of high nonlinear loads in power systems, causing non-sinusoidal currents and voltages, leads to negative technical consequences and economic losses for the power system and non-distorting consumers. Currently, there are no practical recommendations on choosing the lengths of power lines for supplying high nonlinear loads considering their negative impact on power quality indicators.THE PURPOSE. The study analyzes the conditions for the occurrence of harmonic resonant overvoltages in a power supply scheme of a nonlinear load. METHODS. The main methods used for the study include the compilation of equivalent diagrams of the electrical network elements and calculation of currents and voltages in lumped-element circuits. The Fourier series decomposition is applied to analyze non-sinusoidal currents and voltages. Using simulation models in MATLAB Simulink environment, the conditions for the occurrence of higher harmonic resonances at different lengths of 35, 110, and 220 kV power transmission lines and different power ratings of the power system are determined.RESULTS. Calculated resonant lengths of overhead power lines 35-220 kV, supplying a nonlinear load, at which resonant overvoltages occur in the electrical network on higher harmonics with numbers from 3 to 49, were obtained. The resonant lengths of power transmission lines on particular harmonics were determined taking into account the impact of the power supply system reactance. The obtained combinations of resonant line lengths and system reactances are proposed to be considered in the design of external power supply schemes for nonlinear loads to eliminate harmonic overvoltages. The calculations in this study provided an explanation for the abnormal levels of currents and voltages of the 35th and 37th harmonics in the external power supply scheme of an aluminum plant.CONCLUSION. Practical recommendations are given for choosing the lengths of 35-220 kV power transmission lines in power supply systems with high nonlinear loads to eliminate resonant overvoltages. The results of determining the resonant lengths of power transmission lines agree with the data from measuring experiments in an operating power system.